Modern Classification of Respiratory Diseases: Innovations in the International Classification of Diseases of the 11th Revision - Nevzghoda, Oleksandr (SSP Modern Pharmacy and Medicine, 2024)
A comprehensive analysis has been performed on the innovations in the classification of respiratory diseases introduced in ICD-11, comparing it with the previous ICD-10 version. This analysis underscores the critical importance of implementing a more detailed and systematic approach to categorizing diseases of the respiratory system. The enhancements found in ICD-11 have been proven to open up new opportunities for the timely and high-quality provision of medical and pharmaceutical care. This is particularly significant for patients suffering from various injuries, including those resulting from traffic accidents, participation in combat operations, and thoracic injuries. The updated classification system in ICD-11 allows for more precise diagnosis and treatment plans, which is essential for improving patient outcomes. By providing a more granular level of detail in disease categorization, healthcare professionals can better understand the nuances of respiratory conditions. This leads to more effective communication among doctors, pharmacists, and patients, thereby improving the legal and professional relationships within the healthcare system. Integrating the ICD-11 classification into educational and training programs is essential for advancing the qualifications of specialists. By incorporating it into curricula and professional development programs, medical practitioners can stay abreast of the latest advancements in disease classification and patient care. This integration is also vital for eliminating medical errors, as a more detailed classification system reduces the likelihood of misdiagnosis and improper treatment. Furthermore, adopting ICD-11 supports the ongoing development of the healthcare sector in Ukraine. It aligns the country's medical practices with international standards, facilitating better collaboration with global health organizations. This alignment is crucial for enhancing the overall quality of healthcare services provided to the population. In conclusion, the transition to ICD-11 represents a significant advancement in the classification of respiratory diseases. Its implementation is imperative for improving medical and pharmaceutical care, enhancing specialist training programs, and strengthening the doctor-pharmacist-patient relationship. Embracing this updated classification system will not only reduce medical errors but also contribute to the further development of Ukraine's healthcare sector.